A mini-review of carbon-resistant anode materials for solid oxide fuel cells. Issue 21 (12th October 2021) - Tao, Zetian; Fu, Min; Liu, Yong
Abstract : A comprehensive overview is presented of recent developments as well as trends of carbon-resistant anode materials using hydrocarbon as fuel. Abstract : This paper provides a short review of the recent developments and predicts the future trends in anode materials for solid oxide fuel cells using hydrocarbons as fuels. Various anode materials are summarized and evaluated, such as Ni-based anode, as well as perovskite structure materials and different materials used as functional layers for reforming and catalyzing hydrocarbon fuels. The cell performance and the long-term stability based on the anode materials above are also discussed in the review. To highlight progress, potential anode materials and anode structure are predicted, to help readers search information and find possible research areas.